The study on Data Warehousing: Explanation with Suitable Example (International Journal of Engineering and Computer Science, 2018)
This paper incorporates procedures, protocols, system and constructs a utilitarian tool to generate a factual resource, from one big storehouse by collecting, organizing, storing data from different databases and is available for various kind of quarries which can directly be handled and is utilized for relevant analysis. Various literature is studied and evaluated related to data warehouse concepts, design and application before wiring this paper.